A CASE OF BAIQ NURIL IN MEDIA: SARA MILLS’ CRITICAL DISCOURSE ANALYSIS - Soraya Ramli; Faiz Afio Dhiarafah; Diah Merrita (STBA LIA - Jakarta, 2019)
Writing in the media, a journalist can create his/her own framing, to be in favor or bias. The framing created will show the subject, the object, the victim or the perpetrator of a case from the point of view of the journalist. This study focuses on the position of subject, object, reader, and the ideology in PRI media and The Sydney Morning Herald media in the case of Baiq Nuril Makmun. The research uses a descriptive qualitative method and analyzed by using discourse analysis framework of Sara Mills. The result of data analysis in the articles show that Jokowi and Nuril are mostly put as subject. On the other side, Nuril is also written as object. Furthermore, based on reader position, the authors mostly use pronoun ‘he’, ‘her’, and ‘she‘. By using third person pronoun, readers are in the position of outsiders which can follow the storyline objectively from both of subject and object position. The ideology of the articles show that a leader uphold justice and solve injustice case that is received by Nuril because she becomes a victim two times, of the immoral action and the violation of Electronic Information and Transactions law.